Association of adolescents' knowledge, attitude, and practices on nutrition labels and their nutritional status. - Nguyen, M. F. R.; Orillo, A. T. O.; Hagos, R. A. F.; Javier, C. A. Z.; Alcantara, R. M.; Talavera, M. T. M. (2003)
The purpose of the study was to establish the association of knowledge, attitude, and practices (KAP) on nutrition labels in relation to the nutritional status of adolescents. It was found that the respondents had high KAP ratings on nutrition labels, indicating the respondents' high knowledge on nutrition labels, positive attitude towards nutrition labels, and practice on nutrition labels. Despite high KAP ratings, the study found that KAP and nutritional status has weak (r=0.023, p=0.645) relations. It can be inferred that nutrition labelling alone is insufficient to improve the nutritional status of the group. Other contributing factors such as food habits, social influence, and accessibility to source of food with nutrition labels; information dissemination mechanisms; and presence of diseases are to be determined in order to further elucidate the association between nutrition labels and nutritional status.
Keywords: Nutritional status